Students' Generated Questions Quality by Developing STEM-based E-Module in Science Learning - Annisa Nurramadhani; Suci Siti Lathifah; Irvan Permana (Tadris Biologi Fakultas Ilmu Tarbiyah dan Keguruan IAIN SYEKH NURJATI CIREBON, 2020)
Questioning skills, which are identified as higher-order thinking skills, are needed nowadays. In reality, some of the students, including university students, still lacking in confidence to pose their questions. The teaching materials and method that can develop students' questioning skills, such as electronic modules which developed based on industrial revolution 4.0 and adjusted to students' demand as the millennial generation, are necessary. The electronic module integrates with STEM learning is the best way to solve the students' questioning skills problem. The research purpose is to develop a STEM-based E-module to investigate the development of students' questions quality. The research method used in this research are R&D with design ADDIE (Analyze, Design, Develop, Implementation, and Evaluation), while the E-Module are implemented to the students, the qualitative descriptive method is used. The instrument used to collect some data on this research are video transcription, application transcription, reading test, and questionnaire. This research has been conducted on 26 university students who took Science Environmental Technology and Social (SETS) course. Questions' quality rubrics are used to analyze the data. As a result of this research, the implementation of developed STEM-based E-Modules is achievable. After implementation, the result of the student's question quality in general, including both pojok inquiry and pojok eksplorasi activity, is attained. There are improvements shown from activity 1 and activity 2 on pojok inquiry activity but decreased in activity 3. As for pojok eksplorasi, students’ generated question quality is improved gradually. It can be concluded that students’ generated questions quality is slightly developed, which means that it is attained at the beginning of the open question category as higher-level quality. The novel finding of this research is the question’s quality from the lecturer might have some influence on the quality of students’ questions.